A Contextual Teaching and Learning Method to Enhance the Critical Thinking Abilities of Children with Special Needs - Sari, Wanda Kharisma; Novianti, Ranti; Dewantoro, Dimas Arif (Jurnal Ilmu Pendidikan, 2023)
Critical thinking ability is a crucial cognitive skill that needs to be developed for students with special needs. Critical thinking involves the capacity to analyze, evaluate, and solve problems in a logical and rational manner. Among students with special needs who have diversity in physical, motor, cognitive, and socio-emotional aspects, particular attention is required, especially in critical thinking abilities. The critical thinking abilities of visually impaired, hearing impaired, and physically disabled students lie in providing simple explanations and offering more advanced explanations with the assistance of teachers. The aim of this study is to determine the improvement in critical thinking abilities of children with special needs (visually impaired, hearing impaired, and physically disabled) in the subject of science before and after using the Contextual Teaching and Learning (CTL) method. This research employs a quantitative approach with a quasi-experimental design called interrupted time series. The interrupted time series design is utilized to measure the dependent variable at multiple time points. The study involves four measurements: an initial observation and three post-intervention observations. The instrument employed is observation, which contains critical thinking indicators. The hypothesis is tested using the Wilcoxon sign rank test. The research results indicate an enhancement in critical thinking abilities among students with special needs after being subjected to the Contextual Teaching and Learning (CTL) intervention. The score difference between the first observation and the fourth observation is 63.125, and the fourth observation is 80.375. For visually impaired students, critical thinking abilities in terms of explaining a condition or concept and constructing arguments improved. Hearing-impaired students experienced improvements in sub-indicators such as identifying terms, considering source credibility, and building arguments. Physically disabled students demonstrated improvement in aspects like formulating alternative solutions, answering “why” questions, interpreting statements, and providing reasons.